The president's mane is missing! - Angleberger, Tom (Angleberger, Tom. Inspector Flytrap, 2016)
Hoping to become the world's greatest detective, Inspector Flytrap, a Venus Flytrap, assisted by his assistant, Nina the Goat, investigates a thrilling mystery at the Capitol Building at the request of President Horse G. Horse.